Diacylglycerol Enhances the Effects of Alpha‐Linolenic Acid Against Visceral Fat: A Double‐Blind Randomized Controlled Trial. Issue 10 (29th August 2017) - Saito, Shinichiro; Mori, Atsuko; Osaki, Noriko; Katsuragi, Yoshihisa
Abstract : Objective: To investigate the effect of alpha‐linolenic acid‐rich diacylglycerol (ALA‐DAG) compared with alpha‐linolenic acid‐rich triacylglycerol (ALA‐TAG) on visceral fat area (VFA) in people with overweight. Methods: Subjects with overweight were recruited to a randomized, double‐blind, controlled, parallel‐group designed trial and randomly allocated to two groups that consumed either 2.5 g/d ALA‐TAG or ALA‐DAG for 12 weeks. Two 4‐week nontreatment periods were placed before and after the treatment period. One hundred fourteen subjects ( n = 57 in the ALA‐TAG group, n = 57 in the ALA‐DAG group) were enrolled into the analysis set for efficacy evaluation. Results: The VFA and BMI were significantly decreased by the ALA‐DAG treatment with a treatment‐by‐time interaction compared with the ALA‐TAG treatment ( P < 0.05). Additionally, the change from baseline of the fasting serum TAG concentration at week 12 was significantly decreased by ALA‐DAG treatment compared with ALA‐TAG treatment ( P < 0.05). Safety parameters such as urinary measurements, hematologic parameters and blood biochemistry, and the incidence of adverse events did not differ significantly between groups, and no ALA‐DAG–associated adverse effects were detected. Conclusions: Incorporation of ALA‐DAG in a regular diet for 12 weeks may lead to a reduction in VFA, BMI, and serum TAG in men and women with overweight.